Amplicon-based sequencing revealed potential microbiologically influenced corrosion in the interim storage for spent fuel of RSG-GAS, Serpong, Indonesia - IRAWAN SUGORO; DIANNISA SYAHWA RAHMA FADILA; MEGGA RATNASARI PIKOLI; FERI EKO HERMANTO; FIRDAUS RAMADHAN; SYALWA ERSADIWI SHALSABILLA; ADE CICI; MOHAMMAD SYAMSUL RIJAL; DYAH SULISTYANI RAHAYU; MARHAENI JOKO PUSPITO; DINDA RAMA HARIBOWO; DEVITA TETRIANA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sugoro I, Fadila DSR, Pikoli MR, Hermanto FE, Ramadhan F, Shalsabilla SE, Cici A, Rijal MS, Rahayu DS, Puspito MJ, Haribowo DR, Tetriana D. 2023. Amplicon-based sequencing revealed potential microbiologically influenced corrosion in the interim storage for spent fuel of RSG-GAS, Serpong, Indonesia. Biodiversitas 24: 5391-5398. Interim storage of spent fuel (ISSF) corrosion can negatively impact nuclear power plant maintenance, specifically concerning safety, financial costs, and regulatory compliance. Besides chemical reactions, microbiologically influenced corrosion (MIC) also primarily occurred. Sulfate-reducing bacteria (SRB) plays a significant role in the development of MIC. The quantitative of MIC research has never been conducted in the ISSF - Multipurpose nuclear reactor of G.A. Siwabessy (RSG-GAS). So, this study aims to monitor the potential MIC development in the ISSF of RSG-GAS pool and canal through bacterial diversity analysis using total plate count (TPC) and metagenomic approach. TPC results showed that SRB was identified in the canal of ISSF but not in the pool site. However, metagenomics analysis revealed higher diversity measures in the pool than in the canal sites. Staphylococcus sp. was the most abundant species in both sites, with a relative abundance greater than 85%. The number of SRB and MIC-related bacteria was higher in the canal than in the pool, both from TPC and metagenomic analysis. Several SRB taxa were identified, such as Desulfobulbus mediterraneus, Desulfobulbus sp., Desulfofustis sp., Desulfovibrio sp., and Truepera sp. The potential MIC development also strengthens by diversity-based metabolic pathway prediction, which mainly displayed sulfur oxidation and sulfate reduction pathways in the canal system.